Conversion of SISO processes with multiple time-delays to single time-delay processes. (May 2018) - Luan, Xiaoli; Chen, Qiang; Albertos, Pedro; Liu, Fei
Highlights: Plants with multi time delays are considered. The model is converted to a single time-delay by means of a precompensator. The strategy is applied to different examples, dealing with unstable and NMP plants. Abstract: There are many processes with multiple time-delays. These may appear in the direct path or in some feedback path. In this paper, a pre-compensator is designed in order to convert a multiple time-delays process to one with a single time-delay in the forward path. On this simpler model, any well-established approach to design the control for input/output time-delay plants can be applied. The proposed method is directly applicable to stable plants with multiple time-delays, including in the feedback path, and it can be extended to unstable plants with some constraints. Some numerical examples and case studies are provided to illustrate the application of the proposed algorithms.